2010
DOI: 10.1177/0890334410369481
|View full text |Cite
|
Sign up to set email alerts
|

Review: Breastfeeding Peer Counseling: From Efficacy Through Scale-Up

Abstract: There are a growing number of publications evaluating various breastfeeding peer counseling (PC) models. We have systematically reviewed a) the randomized trials assessing the effectiveness of breastfeeding PC in improving rates of breastfeeding initiation, duration, exclusivity and maternal and child health outcomes; and b) scientific literature describing the scale-up of breastfeeding PC programs. Twenty-six peer-reviewed publications were included in this review. The overwhelming majority of evidence from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
151
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 38 publications
3
151
0
3
Order By: Relevance
“…A recent review of breastfeeding promotion summarised the small amount of evidence from Africa. 6 In the past decade, most studies in which EBF was promoted in sub-Saharan Africa had been undertaken within the framework of prevention of mother-to-child transmission of HIV 1 to assess whether EBF could increase HIV-free survival. 4 The results indicated that intensive interventions could lead to near-universal adherence to EBF.…”
Section: Summentioning
confidence: 99%
“…A recent review of breastfeeding promotion summarised the small amount of evidence from Africa. 6 In the past decade, most studies in which EBF was promoted in sub-Saharan Africa had been undertaken within the framework of prevention of mother-to-child transmission of HIV 1 to assess whether EBF could increase HIV-free survival. 4 The results indicated that intensive interventions could lead to near-universal adherence to EBF.…”
Section: Summentioning
confidence: 99%
“…Breast-feeding education and support delivered by paraprofessionals has been shown to be at least as effective as, if not more effective than, education and support delivered by health professionals (9)(10)(11) . Peer counsellors are typically women recruited from the community who have had a positive breast-feeding experience and are trained to provide breastfeeding support, education and technical assistance to their peers (12,13) . This model has demonstrated efficacy in improving breast-feeding initiation rates, breast-feeding duration and exclusive breast-feeding duration in the lowincome population (14) .…”
mentioning
confidence: 99%
“…1,2 This means that early education, promotion of breastfeeding may start premarital, preconception or at least during pregnancy. [5][6][7][8] The fact that exclusive breastfeeding has not been practiced to its maximum potentials in Indonesia is supported by year 2012 and 2014 Health Statistics which showed that only 42% and 52.3% of breastfeeding mothers did so.…”
Section: Introductionmentioning
confidence: 99%
“…Some of breastfeeding problems may not surface if women had been informed about the benefits of breastfeeding and prepared mentally for exclusive breastfeeding since they were young. 5,6 University students are in unique position as to being recipients of valid information on breastfeeding issues. University students will often play an important role in information exchanges between their peers, family and the community as a whole, during education period or after they graduate.…”
mentioning
confidence: 99%
See 1 more Smart Citation